Is the tea or teacup good? The effect of visual and haptic sensory processing of teacups on the perception of tea flavor - Yang, Su-Chiu; Hsu, Li-Chieh (Frontiers in Psychology, 2024)
Prior research on the relationship between the taste, aroma and drinking utensils of beverages tends to focus on topics such as alcohol, sparkling beverages, juice, coffee, and hot chocolate. There is limited research focused on the interdependence between the perception of teacups and the tea taste. The literature has not yet found any research covering the impact of visual shape and the tactile sensation of teacups on the perception of tea flavor. Therefore, this study proposed six hypotheses related to the teacup shape and texture, teacup preference and taste and smell of tea. This study involved experimental design and questionnaire data collection, using a convenience sampling method to recruit 102 participants voluntarily. The research results are: (1) Age and gender have an impact on the taste and aroma perception of tea; (2) The width, height, rim thickness and smoothness of the teacup surface do have an impact on the perception of taste and fragrance of tea. (3) The preference of teacup played an intermediary effect between tea taste and the shape and texture of teacup. The implications of these findings on the perception of tea flavor are discussed.